INSTITUIÇÕES MUNICIPAIS DE EDUCAÇÃO SUPERIOR NO BRASIL: HISTÓRIA E POLÍTICA EM PAUTA (1995 – 2021) - CLEIA SIMONE FERREIRA (2022)
With a historical basis on higher education in Brazil, this study discusses the structural and organizational complexity of the Municipal Institutions of Higher Education (IMES), its importance in the context of the interiorization of higher education and the process of commodification of education, which constitutes the appropriation of education as a commodity manipulated according to its exchange value and the consequent accumulation of capital. The aim is to answer the problem discussed in this research based on the following question: how is the movement of higher education policies for the IMES in Brazil (1995-2022) and how do these present the characteristics of the public and the private? The study hypothesis is that: the IMES played an important role in the internalization of higher education in Brazil, but the complexity of their public-private structures and the commodification of higher education ended up compromising their performance, even more so because, since the Federal Constitution (CF/1988), the creation of new IMES was not allowed. The general objective of the study was to analyze the movement of higher education policies for IMES in Brazil (1995-2022) between the public and the private sectors. For the development of this purpose, the following specific objectives were determined: - explain higher education policies in Brazil (1995 to 2022); - examine the policies that systematize the IMES in Brazil and - analyze the main characteristics of the institutional organization of the IMES in Brazil. In order to reach the established objective, a qualitative research was carried out with the collection of bibliographic information in the field of secondary data and documents. As observed in the surveys carried out, the 1990s, with emphasis on the year 1995, the beginning of the Fernando Henrique Cardoso Government, was the period with the highest number of IMES, with a reduction occurring from the year 2000 and a process of contradiction between public and private between 2002 and 2019, which ranged from 59 to 71 in the Governments of Luiz Inácio Lula da Silva and Dilma Rousseff while, in the Government of Jair Messias Bolsonaro, it went from 59 to 60 units. that the IMES are structures under public-private action initiated in Brazil in the state of São Paulo, the first stage of these forms of institutions, with the purpose of interiorizing higher education. Finally, it was concluded that the structural and organizational complexity of the IMES is related to the historical process of national policies, especially since CF/1988. In addition, the IMES contributed/contribute to the internalization of higher education, through a rearrangement in its structural organization. The characteristic of a public-private HEI guaranteed its continuity, but not the possibility of creating new institutions. However, under the changes in the logic of capital, aspects of the process of commodification of education were developed in most of the existing HEIs. In the search for survival, the IMES developed an important role in the offer of education in the interior of Brazil, but the offer of education as a commodity compromises the performance of these HEIs that resist, but that are captured by the movement of the capitalist system. Keywords: Higher education; commodification; public-private; Interiorization.